PELAJARAN HIDUP DI SEKOLAH: EKSPLORASI TOLERANSI ANTAR SISWA DI SMP N 1 BONTANG - Siswoko, Heri; Hajaroh, Mami; Eliasa, Eva Imania; Azizah, Nur; Fauzi, Lailla Affianti (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
The problem of tolerance in schools arises due to a lack of understanding of diversity, social, communication difficulties, and injustice in treatment so that the role of education is needed in shaping students who have an attitude of tolerance. The purpose of this study is to explore the level of understanding and practice of tolerance among students. This research is a quantitative study, with data acquisition through the survey method. The data collected will be analyzed descriptively to identify the level of understanding of students' tolerance attitudes in everyday life in the school environment. The results of this study indicate that although students at SMP N 1 Bontang are divided into several classes, and have religious differences, the students have a good level of understanding and practice of tolerance as evidenced by the results of the analysis assessment. This illustrates that the educational efforts and school environment at SMP N 1 Bontang was successful in promoting tolerance among students who have diverse backgrounds.